THE EFFECT OF SWEET ORANGE PEEL OIL ADDITIVE ON VIRGIN COCONUT OIL COMBUSTION CHARACTERISTIC - Sangkilang, Elvinda; Sasmoko, Sasmoko; Wijayanti, Widya; Wardana, ING (International Journal of Mechanical Engineering Technologies and Applications, 2026)
Biodiesel is a viable renewable alternative energy source to develop and further utilize in order to maintain environmental sustainability. Virgin coconut oil (VCO), which is plentiful in Indonesia, is one of several vegetable oils that has the potential to be converted into biodiesel. The viscosity and density of VCO are high due to the glycerol and three fatty acid components, which have a notable impact on both the performance and efficiency of combustion. Sweet orange peel oil additive plays an important role in enhancing combustion because its chemical compound, which has an aromatic structure, can influence molecular interactions, thereby enhancing the kinetic energy of fuel molecules, which consequently improves the combustion performance of vegetable oil. The combustion process was visually examined using the high-speed camera Canon 600D. The results show that the flame dimensions increased and its color changed from orange to blue, indicating that utilization of sweet orange peel oil could enhance the combustion energy values, the blue color has a greater energy level in the visible light spectrum than the orange hue. Furthermore, it was noted that the ignition delay time showed a decrease in duration, but the burning time showed a comparable pattern of being extended. Vegetable oil deforms and becomes more reactive due to the disruption of its molecular structure caused by the magnetic field of the aromatic structure found in sweet orange peel oil. This phenomenon was confirmed by molecular dynamic simulation using the HyperChem 8.0.10 software.